(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
For a number of new laser technology processes, it is essential to plan an experimental plan for primary experimental engineering activities in terms of quality. The assessment of the critical power density to reach the melting or evaporation temperature of the surface with a suitable theoretical model is an important stage in the development of a particular manufacturing technology. With the help of numerical experiments, this report provides a method for pre-examining the influence of wavelength on the laser technological process. The calculations are performed with a specialized program, running MATLAB. A series of temperature fields were obtained at a change in power density and wavelength at laser impact for concrete types of structural steel. The temperature dependence of the optical and thermo-physical characteristics of the material is also reporded. The analysis is made for laser technology complexes working with lasers emitting in the ultraviolet, visible, near and distant infrared areas. For these wavelengths the critical power density of melting and evaporation is determined.